The Concept of Oceanian Sovereignty in the Context of Deep Sea Mining in the Pacific Region - Tilot, Virginie C.; Guilloux, Bleuenn; Willaert, Klaas; Mulalap, Clement Y.; Bambridge, Tamatoa; D’Arcy, Paul; Mawyer, Alexander; Gaulme, François; Kacenelenbogen, Edwige; Jeudy de Grissac, Alain; Moreno Navas, Juan; Dahl, Arthur (Frontiers in Marine Science, 2021)
Based on an interdisciplinary experience addressing traditional dimensions in marine resource management in the Pacific, the socio-ecological interconnectivity between island communities, the ocean realm and the legal context concerning the management of seabed resources (Tilot, 2006, 2010; Tilot et al., 2018, 2021a,b; Mulalap et al., 2020; Willaert, 2020a,b, c; 2021; DOSI, 2021), this paper proposes to discuss the relevance and efficacy of the concept of “Oceanian Sovereignty” (Bambridge et al., 2021) in the context of Deep Sea Mining, from the different legal, environmental, anthropological, social, political, and economic science perspectives. The policies and practices developed in the Pacific in this context could well serve as a suitable model elsewhere to reconcile competing perspectives in addition to sustaining the Human Well-being and Sustainable Livelihoods (HWSL) and the health of the Global Ocean.